Improving English pronunciation skills using tongue twister technique through Twistify application in junior high school - Shella Nabilla; Theresia Cicik Sophia Budiman; Maria Yosephin Widarti Lestari (Universitas Aki, 2023)
The objective of this research was to find out the result of the pronunciation skills of students in Junior High School before and after being given treatment using the tongue twister technique through the Twistify application. The populations in this research were students of class VIII SMP Negeri 1 Tayu, Pati, Central Java, Indonesia. The sample consisted of 34 students from class VIII B. The researcher used pre-experimental and implemented one group pre-test and post-test design. Based on the results, there was an increase in students’ pronunciation skills from the pre-test with a mean score of 58.35 to the post-test with a mean score of 80 and an increase from the pre-test to the post-test by 37.10%. From the data calculation, the researcher found that the t-test result was 46.442, and the value of df (degree of freedom) was 33. The t-table value was obtained from df = 33 so that t-table = 2.035, so (t0 > tt), 46.442 > 2.035. The Alternative Hypothesis (Ha) was accepted, and the Null Hypothesis (H0) was rejected. Thus, there was a significant difference between students’ pronunciation skills before and after being given treatment using the tongue twister technique through the Twistify application.